Additional Learning is as a Factor of Mental Health - Muazzam To’lqinovna, Isakova (International Journal of Psychosocial Rehabilitation, 2020)
In this article we have made an effort to analyze how education is important for an individual’s mental health. We would like to have an insight into the Fergana Region’s knowledge of people toward mental health. According to our questionnaire, there are 15 factors that play an essential role in the state of people’s mental health. As a result of our survey, 27.8 percent of respondents have selected the additional learning (learning of cooking, knitting, curing, making up, and so on that helps to facilitate daily duties) among 15 factors.